Effects of Natural and Synthetic Preservatives on the Microbial, Physicochemical, and Shelf-Life Characteristics of Dried Beef Under Ambient Storage Conditions - Nnenna , Omorordion; C, Wami Princess (Indonesian Journal of Modern Science and Technology, 2026)
This study investigated the effects of natural (ginger and garlic) and synthetic (potassium sorbate and sodium nitrite) preservatives on the microbial quality, physicochemical quality, and shelf life of dried beef stored under ambient conditions. Over a 9-day storage period, samples were analyzed for total bacterial counts, coliforms, staphylococcal and fungal counts, moisture content, and total volatile base nitrogen (TVB-N). The results revealed that untreated samples deteriorated rapidly, showing high microbial proliferation (total viable count increasing from 0.00 to 5.5 log CFU/g) and significant biochemical spoilage, with TVB-N rising from 7.25 to 24.60 mg N/100 g. In contrast, treated samples, particularly those preserved with potassium sorbate and sodium nitrite, showed markedly lower microbial counts (3.55 to 5.5 log CFU/g), controlled TVB-N values (6.70 to 15.00 mg N/100 g), and reduced moisture loss (30.40 ± 0.12% to 27.00 ± 0.18%) compared to the control. Microorganisms isolated revealed Bacillus subtilis, Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa as the dominant bacteria, while Aspergillus niger, Saccharomyces cerevisiae, and Candida spp. were the major fungi. Natural preservatives (ginger and garlic) exhibited antimicrobial activity, especially when combined, while synthetic preservatives demonstrated superior inhibitory and stabilizing effects (p < 0.05). Overall, the study concludes that both natural and synthetic preservatives significantly enhanced the safety and shelf life of dried beef, with synthetic treatments proving most effective. Nonetheless, natural preservatives such as ginger and garlic represent promising, health-friendly alternatives that can be optimized for sustainable meat preservation.